A Highly Reversible, Dendrite‐Free Lithium Metal Anode Enabled by a Lithium‐Fluoride‐Enriched Interphase. Issue 12 (14th February 2020) - Cui, Chunyu; Yang, Chongyin; Eidson, Nico; Chen, Ji; Han, Fudong; Chen, Long; Luo, Chao; Wang, Peng‐Fei; Fan, Xiulin; Wang, Chunsheng
Abstract: Metallic lithium is the most competitive anode material for next‐generation lithium (Li)‐ion batteries. However, one of its major issues is Li dendrite growth and detachment, which not only causes safety issues, but also continuously consumes electrolyte and Li, leading to low coulombic efficiency (CE) and short cycle life for Li metal batteries. Herein, the Li dendrite growth of metallic lithium anode is suppressed by forming a lithium fluoride (LiF)‐enriched solid electrolyte interphase (SEI) through the lithiation of surface‐fluorinated mesocarbon microbeads (MCMB‐F) anodes. The robust LiF‐enriched SEI with high interfacial energy to Li metal effectively promotes planar growth of Li metal on the Li surface and meanwhile prevents its vertical penetration into the LiF‐enriched SEI from forming Li dendrites. At a discharge capacity of 1.2 mAh cm −2, a high CE of >99.2% for Li plating/stripping in FEC‐based electrolyte is achieved within 25 cycles. Coupling the pre‐lithiated MCMB‐F (Li@MCMB‐F) anode with a commercial LiFePO4 cathode at the positive/negative (P/N) capacity ratio of 1:1, the LiFePO4 //Li@MCMB‐F cells can be charged/discharged at a high areal capacity of 2.4 mAh cm −2 for 110 times at a negligible capacity decay of 0.01% per cycle. Abstract : A dendrite‐free lithium (Li) metal anode for Li metal batteries (LMBs) is realized by using surface‐fluorinated mesocarbon microbeads (MCMB‐F) as substrate. During the lithiation process, the fluorinated graphite on the outermost surface of MCMB‐F is reduced in situ to form a robust lithium‐fluoride‐enriched solid electrolyte interphase, providing an efficient avenue for LMBs with high Li metal coulombic efficiency and no Li dendrite growth.